The Effect of Remineralizing Agents With/Without CO2 Laser Irradiation on Structural and Mechanical Properties of Enamel and its Shear Bond Strength to Orthodontic Brackets - Ghadirian, Hannaneh; Geramy, Allahyar; Shallal, Waleed; Heidari, Soolmaz; Noshiri, Nooshin; Keshvad, Mohammad Ali (Journal of Lasers in Medical Sciences, 2020)
Introduction: Remineralizing agents may be used for the treatment of white spot lesions (WSLs) prior to bracket bonding. However, some concerns exist regarding their possible interference with the etching and bonding process, negatively affecting the bond strength. This study aimed to assess the effect of two remineralizing agents with/without CO2 laser irradiation on the mechanical properties and shear bond strength (SBS) of demineralized enamel to the orthodontic bracket. Methods: This study evaluated 60 premolar teeth in 6 groups (n=10) as follows: (I) sound enamel, (II) demineralized enamel, (III) Nupro remineralizing agent (N), (IV) Nupro and CO2 laser (N/L), (V) Teethmate remineralizing agent (T), and (VI) Teethmate and CO2 laser (T/L). The remineralizing agents were applied to the enamel surfaces after their immersion in a demineralizing solution for 5 days. In groups IV and VI, the CO2 laser with a 10.6 μm wavelength, 10 ms pulse duration, a 50 Hz repetition rate, 0.3 mm beam diameter and 0.7 W power was irradiated after applying the remineralizing agents. Brackets were bonded to the enamel surfaces and SBS was measured by a universal testing machine. For the assessment of enamel microhardness, 20 sections of molar teeth were divided into 4 groups (n=5; N, N/L, T, T/L) and their microhardness was measured before demineralization, after demineralization and after remineralization. X-ray diffraction (XRD) analysis, field-emission scanning electron microscopy (FESEM) and energy-dispersive spectrometry (EDS) were carried out to assess the formation of hydroxyapatite. The atomic percentages of the C, O, P, Ca, Na, Si, F and Ca/P ratio were determined by EDS analysis. Results: The SBS significantly decreased in group II (P < 0.001). There was no significant difference among the groups I, III, IV, V and VI (P < 0.05). This finding was similar to the microhardness results, which showed an increase in microhardness after remineralization (P < 0.05), with no difference among the remineralizing agents. The Ca/P ratio was the highest in the Nupro group and the lowest in the demineralized group. Conclusion: Remineralizing agents can significantly improve the microhardness and structural properties of demineralized enamel to a level similar to that of sound enamel with no adverse effect on SBS to orthodontic brackets.